INIBIÃ‡ÃƒO BACTERIANA CAUSADA POR POLEM COLETADO PELAS ABELHAS (ð˜ˆð˜±ð˜ªð˜´ ð˜®ð˜¦ð˜ð˜ð˜ªð˜§ð˜¦ð˜³ð˜¢ L.) - Joly, S. (REVISTA DE AGRICULTURA, 2020)
INIBIÃ‡ÃƒO BACTERIANA CAUSADA POR POLEM COLETADO PELAS ABELHAS (ð˜ˆð˜±ð˜ªð˜´ ð˜®ð˜¦ð˜ð˜ð˜ªð˜§ð˜¦ð˜³ð˜¢ L.)